Burden of Undiagnosed Hypertension among Adults in Urban Communities of Southwest Ethiopia - Mogas SB; Tesfaye T; Zewde B; Tesfaye Y; Kebede A; Tadesse M; Gudina EK; Tamiru D; Dadi LS (Dove Medical Press, 2021)
Solomon Berhanu Mogas,1 Temamen Tesfaye,2 Belay Zewde,3 Yonas Tesfaye,4 Ayantu Kebede,1 Mulualem Tadesse,5 Esayas Kebede Gudina,6 Dessalegn Tamiru,7 Lelisa Sena Dadi1 1Department of Epidemiology, Jimma University, Jimma, Oromia Region, Ethiopia; 2School of Nursing and Midwifery, Jimma University, Jimma, Oromia Region, Ethiopia; 3Department of Biomedical Sciences, Jimma University, Jimma, Oromia Region, Ethiopia; 4Department of Psychiatry, Jimma University, Jimma, Oromia Region, Ethiopia; 5School of Medical Laboratory Science, Jimma University, Jimma, Oromia Region, Ethiopia; 6Department of Internal Medicine, Jimma University, Jimma, Oromia Region, Ethiopia; 7Department of Nutrition and Dietetics, Jimma University, Jimma, Oromia Region, EthiopiaCorrespondence: Solomon Berhanu MogasDepartment of Epidemiology, Jimma University, P.O.Box-378, Oromia Region, EthiopiaTel +251913458961Email solo.berhanu@gmail.comBackground: Hypertension (HTN) is the leading risk factor for mortality due to cardiovascular diseases, it accounts for 7% of global disability adjusted life years. In 2015, it was estimated that around 1.13 billion adults had HTN globally with a high prevalence in low and middle-income countries where the health system is weak to diagnose, treat, and control HTN. Most people with HTN are asymptomatic and go undiagnosed for years. Therefore, the aim of this study was to assess the burden of undiagnosed HTN among adults in urban communities of Southwest Ethiopia.Methods: A community-based cross-sectional study involving 915 adults from June 17 to July 27, 2019 was performed. WHO STEPS questionnaire was used to collect data, and the collected data were entered using Epi Data version 3.1and analyzed using SPSS version 20, respectively. Binary logistic regression was used to check for a possible association between outcome and independent factors. P-value < 0.05 and 95% CI were used on multivariable logistic regression analysis as threshold for significant statistical association.Results: Undiagnosed HTN in the study area was 21.2% (194). Age (AOR=1.04, 95% CI=1.02– 1.05), BMI with overweight (AOR=2.52, 95% CI=1.35– 4.71), triglyceride (AOR=1.83, 95% CI=1.29– 2.59), and waist to hip ratio (AOR=1.62, 95% CI=1.03– 2.54) were factors significantly associated with HTN.Conclusion: As compared to studies performed before, the risk of undiagnosed HTN in the current study was high. Age, BMI, triglyceride, and waist to hip ratios were found to be the significant factors for it. Preventing the risk factors and screening of HTN should be promoted for early detection, prevention, and treatment of the burden of the disease on the population.Keywords: adult, burden, Ethiopia, hypertension, Jimma town, risk, undiagnosed